Language experience during the sensitive period narrows infants’ sensory encoding of lexical tones—Music intervention reverses it - Zhao, Tian Christina; Llanos, Fernando; Chandrasekaran, Bharath; Kuhl, Patricia K. (Frontiers in Human Neuroscience, 2022)
The sensitive period for phonetic learning (6 12 months), evidenced by improved native speech processing and declined nonnative speech processing, represents an early milestone in language acquisition. We examined the extent that sensory encoding of speech is altered by experience during this period by testing two hypotheses: 1) early sensory encoding of nonnative speech declines as infants gain native-language experience, and 2) music intervention reverses this decline. We longitudinally measured the frequency-following response (FFR), a robust indicator of early sensory encoding along the auditory pathway, to a Mandarin lexical tone in 7- and 11-months-old monolingual English-learning infants. Infants received either no intervention (language-experience group) or music intervention (music-intervention group) randomly between FFR recordings. The language-experience group exhibited the expected decline in FFR pitch-tracking accuracy to the Mandarin tone, while the music-intervention group did not. Our results support both hypotheses and demonstrate that both language and music experiences alter infants’ speech encoding.